Properties of TI/CU multilayer coatings - Guchenko, S.A.; Koval, N.N.; Yurov, V.M.; Krysina, O.V.; Zavatskaya, O.N. (Publishing House of the KarSU named after E.A.Buketov, 2018)
In this work, we used the cathodes Ti and Cu. Coatings were deposited on steel samples by the ionplasma method on a vacuum unit while simultaneously spraying the above cathodes. Multilayer coatings were created as follows: Ti was applied for 2 minutes, then Ti+Cu for 2 minutes. A total of 100 layers were applied in an atmosphere of argon and nitrogen.An electron microscopic study was carried out on a MIRA 3 scanning electron microscope of the TESCAN company. The studies were carried out at an accelerating voltage of 20 kV and a working distance of about 15 mm. The optical microstructure was examined on a metallographic microscope Epiquant. The study of the microhardness of the coatings was carried out on a microhardness meter HVS-1000 A. The results of measuring the microhardness of TiN+(Ti+Cu)N in nitrogen show an increase in the hardness of the coating from the standard for titanium nitride TiN values H = 20 to H = 30 GPa. Electron microscopic studies have shown that TiN+(Ti+Cu)N coatings usually have a columnar structure with filamentous grains 2–5 nm in diameter, elongated in the direction of growth. When titanium nitride TiN slides over ordinary carbon steel and at room temperature, the coefficient of friction is 0.9, and the coefficient of friction of the TiN+(Ti+Cu)N multilayer coating decreases by a factor of 3 and does not exceed 0.3. An increase in the hardness of the TiN+(Ti+Cu)N coating and a decrease in the friction coefficient by a factor of 3 together leads to a significant increase in wear resistance. This is especially important for cutting tools.If you add up all the advantages of the obtained coatings, including resistance to high-temperature oxidation and their relatively low cost, then you can expect that TiN + (Ti + Cu) N multilayer coatings will find wide application in the metalworking industry, engineering, energy and some other areas.
Keywords: coating; microstructure; microhardness; friction